Near-Field Induced Reaction Yields from Nanoparticle Clusters - Rosenberger, Philipp; Rupp, Philipp; Ali, Rami; Alghabra, M. Said; Sun, Shaohua; Mitra, Sambit; Khan, Sharjeel A.; Dagar, Ritika; Kim, Vyacheslav; Iqbal, Mazhar; Schotz, Johannes; Liu, Qingcao; et al. (ACS Photonics, 2020)
Ultrafast light-induced molecular reactions on aerosolized nanoparticles may elucidate early steps in the photoactivity of nanoparticles with potential impact in fields ranging from chemistry and medicine to climate science. In situ morphology discrimination for nanoparticle streams when measuring light-induced reaction yields is crucial, but lacking. Here, we experimentally demonstrate, using the reaction nanoscopy technique, that proton momenta from deprotonation reactions induced by intense femtosecond pulses exhibit clear, distinguishable signatures for single silica nanospheres and their clusters. Our findings are supported by classical trajectory Monte Carlo simulations. The results demonstrate an in situ single-shot discrimination method between reaction yields from photoinduced processes on single particles and their clusters. We find that the ionization of clusters dominates at sufficiently low intensities, providing an explanation to resolve previously observed discrepancies between experimental data and theoretical treatments, which considered only single nanoparticles.
CRIS-Team Scopus Importer:2023-04-20
Keywords: atomic and molecular physics; chemical physics; nanophysics; physical chemistry